Scorched earth : Stalin's reign of terror - Baberowski, Jörg (Yale-Hoover series on authoritarian regimes., 2016)
German scholar Jörg Baberowski is one of the world's leading experts on the Stalin era, but his work has seldom been translated into English. This book, an unremitting indictment of the mad violence with which Stalin ruled the Soviet Union, depicts Stalinism as a cruel and deliberate attack on Russian society, driven by "totalitarian ambitions" and the goal of modernizing and rationalizing a backward people. Baberowski takes a twofold approach, emphasizing Stalin's personal role and responsibility as well as the continuity he sees in Communist aims and ideology since 1917. Unlike recent apologist accounts that focus on the challenges of modernization or on the operational complexities of managing the Soviet state, this hard-hitting analysis unequivocally locates the origins of the terror in the culture of violence and the techniques of power. Detailed, well-documented, and including many new details on the workings of the Stalinist state, this powerful work encompasses the dictator's brutal reign from his achievement of total power in 1929 to his death in 1953.--